THE RELATIONSHIP BETWEEN ACADEMIC PRESSURE AND MENTAL HEALTH OF STUDENTS - Fuad Hasan (STIT Pringsewu, 2025)
The mental health of students in higher education has emerged as a critical issue due to increasing levels of academic pressure. This case study examines the relationship between academic pressure and student mental health, highlighting how various stressors such as exams, coursework, and high expectations impact emotional well-being. By synthesizing existing literature on the topic, the study identifies the prevalence of mental health issues among students and the specific academic stressors contributing to anxiety, depression, and burnout. The findings suggest that academic pressure negatively affects student well-being and that institutional support, coping strategies, and mental health services are essential to mitigating these effects. The study concludes with recommendations for universities to address these challenges by revising academic policies, improving mental health services, and fostering a supportive environment for students.